Identification Of Immunogenic Proteins From Cysts And Trophozoites Of Giardia Lamblia By Immunoassay - Roshidi, Norhamizah (2024)
Giardia lamblia exists in two stages in the life cycle; the motile trophozoite and the resistant cyst that is highly adapted to harsh environments, infecting humans and animals with a disease known as giardiasis. Giardiasis is a significant public health concern, with an estimated 280 million symptomatic human infections occurring each year and contributing to 1.6 million cases of diarrheal death in 2016. In Malaysia, cases of giardiasis reportedly ranged from 2.6% to 25% from 1970 to 2000 and rise to 10.4% to 28.3% from 2002 to 2019. However, studies on giardiasis are very limited and mostly focused on the variation of gene expression and vaccine development. Therefore, this study was conducted to characterize Giardia proteins that may lead to a better understanding of Giardia-immunogenic proteins potential for diagnostics and therapeutic applications. The approach of this study involves in-vitro cultivation of G. lamblia trophozoites and cyst in different culture medium, protein extraction and separation using OFFGEL™ as an improved pre-fractionation step prior to immunoassays and mass-spectrometry analysis to identify the identity of potential immunogenic proteins. The maximum number of trophozoites of 9.6 x 106 cell/ml was successfully obtained in the TYI-S-33 medium at pH 7 for 72 hours at 37°C, while the maximum number of cysts of 7.45 x 105 cell/ml was produced in complete modified TYI-S-33 medium containing 0.25 mg/ml of porcine bile at pH 7.8 for 72 hours at 37°C.